PENGARUH PERENCANAAN STRATEGIS DAN PERENCANAAN ANGGARAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH PADA SATUAN KERJA PERANGKAT DAERAH (SKPD) DI PEMERINTAH DAERAH KABUPATEN BANDUNG - Sholiha Kurniavie Ashary (LPPM POLITEKNIK LP3I BANDUNG, 2018)
The phenomenon of the problems that show in the performance accountability of local government agencies is the results of the assessment / AKIP evaluation unsatisfactory, not solely the fault of the process of preparing LAKIP, but rather the shortcomings of the system as a whole AKIP, based on evaluations from AKIP evaluation report and the results of discussions with several government agencies in charge of drafting the report. This study is to clarify the effect of strategic planning (X1) and budget planning (X2) as independent variables, as well as performance accountability reports of government agencies (Y) as the dependent variable. The type of research is descriptive research verification Meanwhile, if viewed based on the method used, the research conducted by the authors included in the survey research methods. Based on the discussion of the results of research using multiple linear regression analysis showed the following results: 1) That the strategic planning variables affect the variable performance accountability of government agencies; 2) That the budget planning variable does not affect the variable performance accountability of government agencies; 3) That the simultaneous strategic planning and budget planning significant effect on performance accountability of government agencies